An empirical assessment of the impact of Development Financial Institutions (DFIs) on Malaysian economy - Islam, Mohd Aminul (Research Academy of Social Sciences, 2015)
This paper aims to investigate the importance of Development Financial Institutions (DFIs) as a significant component of the financial system and their contributions towards promoting and supporting economic development process in Malaysia. We investigated the topics from both conceptual and empirical viewpoints. To analyze their development and contributions we have used total assets and the financing activities of DFIs covering the period 1980 – 2012. Total assets represent the size or development of DFIs while financing activities represent the involvement in promoting economic development. For empirical test, we utilized cointegration method to determine the relationship between per capita real income and the DFIs involvement in economic activities. The investigation revealed that since establishment, the DFIs have been playing important role towards achieving national development agenda by channeling the resources and funds in the economy to meet the demand particularly for medium and long term capital to areas and sectors deemed as strategic for national economic development plan. The empirical results showed that both the variables in the form of total assets and financing activities of DFIs have positive and statistically significant long run relationship with per capita real income suggesting that the DFIs are also important in influencing per capita income in Malaysia.